Barriers to Customer Relationship Management practices: A survey of university libraries in Pakistan: - Bahader, Mir (Malaysian Journal of Library and Information Science, 2022)
The purpose of this study is to find out relationship between customer relationship management (CRM) practices and barriers in university libraries of Pakistan. The study also focused on CRM’s barriers and its correlation with types of university, regions of university and gender. This study adopted correlational research design with survey method based on quantitative data collection. A structured and open-ended questionnaire was distributed among the head/in-charge librarians of universities libraries in Pakistan. The results have demonstrated that major barriers of CRM are financial resources/budget, qualified, experienced and trained staff, human resource satisfaction and motivation, information technology infrastructure, CRM knowledge and understanding by staff, library culture and collaboration, library users, and leadership commitment. Insignificant variations were found in the overall mean score of CRM barriers based on types of university, regions of university, and gender of the respondents. There is a strong negative (inverse) relationship exist among CRM practices and overall barriers as well as its four sub-facets, while three attributes having moderate negative relationship respectively. This study has numerous practical and theoretical contributions about CRM for academic libraries, especially those engaged in customer relationship management strategies, practices and implementation. The results enlighten library employees to be effective, proactive and successful performers for users’ satisfaction, retention and loyalty.